BRAF V600 co-testing in thyroid FNA cytology: short-term experience in a large cancer centre in the UK. Issue 8 (29th May 2014) - Poller, David N; Glaysher, Sharon; Agrawal, Avi; Caldera, Saliya; Kim, Dae; Yiangou, Constantinos
Abstract : Aims: To ascertain whether BRAF V600 mutational analysis is useful for diagnosis of thyroid cancer in thyroid fine needle aspirate (FNA). Methods: Over 8 months thyroid FNAs reported as Thy 3F (neoplasm possible/suggestive of follicular neoplasm ), Thy4 ( suspicious of malignancy ) and Thy 5 ( malignant ) were tested for BRAF V600 mutation and managed as malignant if mutations were present. Results: Of 207 FNAs from 176 patients, 5 were Thy 5, 19 Thy 4, 36 Thy 3f, 13 Thy 3a, 84 Thy 2 and 50 Thy 1. 11 Thy 3f, 15 Thy 4 and 3 Thy 5 FNAs were tested for BRAF V600 mutation. 0 Thy 3F cases, 6 Thy 4 and 1 Thy 5 (24% of the total tested) showed evidence of mutation. Four patients with BRAF V600 mutation underwent surgery to remove all thyroid tissue, two patients received a lobectomy and one patient is awaiting thyroidectomy. All patients with BRAF V600 mutation were found to have malignancy on final histology, with a diagnostic sensitivity for malignancy excluding coincidental microcarcinoma of 43% and specificity of 100%. Conclusions: BRAF V600 mutational analysis can enable single-stage total thyroidectomy for carcinoma if gene mutation is present in preoperative FNA. BRAF V600 co-testing may reduce the need for completion thyroidectomy with implied cost savings and lower patient morbidity associated with completion thyroidectomy when the cytology is inconclusive but where BRAF V600 mutation is identified in preoperative thyroid FNA.